Addressing domain shift in neural machine translation via reinforcement learning - Kumar A.; Pratap A.; Singh A.K.; Saha S. (My University, 2025)
Domain Adaptation (DA) has been a well-known transfer learning algorithm used in Neural Machine Translation (NMT) task. Adding domain-related corpora in training data to train the model boosts the performance of NMT. Many low resource language pairs such as Hindi–Nepali and Spanish–Portuguese, for which sufficient parallel data are not available to train the model, face in-domain data scarcity issue. Non-availability of in-domain training data leads to the use of unrelated corpus in training the model, which degrades the NMT performance. This domain mismatch between training and test data results in a domain shift problem. To tackle the challenge of the domain shift problem in NMT, we propose REINFORCE-based Sentence Selection and Weighting (RSSW) method, which selects pseudo in-domain sentences from out-of-domain data and learns their weights based on Reinforcement Learning. The proposed method leverages the similarity between language pairs by encoding the source and target languages into a common encoding script for language model training. RSSW uses minimum risk training and maximum likelihood estimation as an objective function to train NMT on selected pseudo in-domain sentences. Furthermore, we employ multi-domain and fine-tuning approaches to compare proposed method on Hindi↔Nepali and Hindi↔Marathi language pairs through extensive experimental analysis. From the experimental results, we find that the proposed method outperforms the state-of-the-art and baseline approaches by ∼2 BLEU points in all translation directions of language pairs. © 2022 Elsevier Ltd